Investigation on the contact interface of Au/Zn on CdZnTe (111) B surface. (15th August 2017) - Yang, Liuqing; Min, Jiahua; Liang, Xiaoyan; Liu, Zhaoxin; Lin, Yunpeng; Zhang, Jijun; Wang, Linjun; Shen, Yue; Zhang, Ying; Li, Ming
Abstract: In recent years, the quality and yield of CdZnTe material has steadily increased and now one of the limiting factors in performance of device is due to the quality of the metal contacts. A better understanding of the interface in metal-semiconductor contact can improve the performance of the detector. In this paper, Zn has been introduced as the intermediate layer between Au and CdZnTe (111) B surface. The structure and the chemical properties of Au/Zn-CdZnTe contact interface have been investigated by focused ion beam (FIB) cross section imaging, high resolution transmission electron microscopy (HRTEM) imaging and x-ray photoelectron spectroscopy (XPS) depth profiling. The results indicated that the Zn transition layer would be prone to combine with the dangling bonds of Te atoms on CdZnTe (111) B surface and help to avoid the emergence of the heterogeneous Te oxide (TeO2 /CdTeO3 ) interface layer between the Au film and CdZnTe, contributing to form the impedanceless contact. Moreover, the electronic response of the Au/Zn-CdZnTe interface by using the circular transmission line model (CTLM) demonstrated that the introduction of Zn layer substantially decreased the specific contact resistivity ( ρ c ), presenting a better ohmic performance.